Implementation Of Teams Games Tournament (TGT) Type Learning Model To Improve Mathematics Learning Outcomes Of Class IV Students - Nazira Maghfira; Al Jupri; Babang Robandi (International Conference on Elementary Education, 2023)
This research is aimed to improve the student outcomes study on fourth-grade student Dayah Tanoh in Mathematics in the chapter on the least common multiple and greatest common divisor Team Games Tournament (TGT) cooperative learning model. This study is action research. The subjects of this study were 28 students of four grade classes. This research was done in two cycles through four steps. The data of this study was collected by an observed and objective test. The analysis data of this study used quantitative descriptive and qualitative descriptive. The succeeded indicators were determined when the average of the student's outcomes in Mathematic improved from cycles I to cycles II. The results of the analysis data in this study showed that there was an enhancement in every cycle. Those can be seen in cycles I of classical completeness was 56% and cycles II improved to 88%. The averages of students' activity increase from 3,4 to 4,8 in cycles II. We can conclude that implementation of the TGT Model could increase the student outcomes in Mathematic Subjects and student activities for fourth-grade students in Dayah Tanoh.